Hábitos de lectura - Borja Romero, Paola Marisol (2017)
The present research deals with the theme: reading habits and the development of verbal logical reasoning, this research project seeks to find relevant information about the problem: Poor reading habits in the development of verbal logical reasoning, whose general objetive is to determine the Influence of reading habits on the development of students verbal logical reasoning of “Sagrado Corazón de Jesús” primary school in Latacunga city, using research methodology to establish the importance of developing reading comprehension. For this purpose, a methodology of scientific, analytical and statistical research was used to collect valuable information from various bibliographic sources in order to support the problem. Several instruments and techniques were used collect information and to prepare statistical data that allowed analysis the necessity and feasibility of the proposal. Taking into account the need to strengthen the good habit of reading and incorporate meaningful learning since it is currently one of the primary requirements, which will serve as an ideal reference the constructivist model, this maintains that the teacher is the very constructor of this knowledge, through his experiences. Providing student proactivity, which will raise the student’s self-esteem, by feeling able to issue a consistent criterion due to their ability to reason logically, improving their academic performance and cognitive and social development, as it will be easier to socialize and make constructive criticisms, using the elements of language, which will improve their active participation and social interrelation, prepared to face challenges and provide solutions to the daily problems that are faced in this new society.